Applying two-dimensional principal component analysis (2DPCA) to the early detection of a weak earthquake-induced tsunami: a case study. Issue 1 (2nd January 2017) - Lin, Jyh-Woei
ABSTRACT: Two-dimensional principal component analysis (2DPCA) was performed to detect the two-dimensional ionospheric total electron content (TEC) anomalies associated with an earthquake in Japan and its associated weak earthquake-induced tsunami. TEC data from a time period of five days before the Mw 6.7 earthquake in Miyako, Japan that occurred at 23:06:27 (UTC) on 16 February 2015 were processed. Another TEC data set from the six-hour time period after this earthquake were processed to detect an associated earthquake-induced tsunami. A TEC precursor to this earthquake indicated by the largest principal eigenvalue of 2DPCA was detectable over the epicentre from 04:40:00 to 04:50:00 (UTC) on 15 February 2015. The duration was approximately 10 minutes. A weak earthquake-induced tsunami TEC anomaly was detectable from 23:15:00 to 23:20:00 (UTC) on 16 February 2015. The tsunami TEC anomaly occurred approximately nine minutes after the earthquake with a duration of approximately five minutes. This study confirms that the TEC anomaly that occurred after this earthquake was a weak earthquake-induced tsunami TEC anomaly. It is concluded that 2DPCA is potentially a useful mathematical tool for monitoring ionospheric anomalous fluctuations that could serve as an early warning system for tsunami detection.